Evaluation of the Fulfillment of Political Rights for Persons with Disabilities to Welcome the 2024 General Election - Wiwit Pratiwi; Sherly Nelsa Fitri; Zico Junius Fernando; Jaco Barkhuizen (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
2024 is the year of simultaneous general elections. All citizens can participate, and every vote counts, including that from people with disabilities. This paper aims to determine the fulfilment of the political rights of persons with disabilities in general elections in Bengkulu City to welcome the general elections to be held simultaneously in 2024. This legal paper used an empirical method with a qualitative approach by collecting primary data from persons with disabilities in Bengkulu City. In-depth interviews were used to find out the fulfilment of the political rights of persons with disabilities in the general elections in Bengkulu City. This paper concludes that the political rights of persons with disabilities in elections in Bengkulu City had not been fulfilled optimally. These rights included the rights to (i) be registered to cast a vote, (ii) access polling stations (TPS), (iii) cast their votes confidentially, (iv) receive information, including information about the elections, and (v) take part in elections. This was because the organizers, namely KPU, failed to play their role optimally. They failed because they had limited funding and persons with disabilities themselves were self-isolating and did not know their political rights.